Silence Speaks Volumes: The Effectiveness of Reticence for Repairing Trust Violations - FERRIN, Donald L. (Institutional Knowledge at Singapore Management University, 2005)
Prior research on trust repair has focused primarily on the effects of apology and denial. We recognize another form of verbal response: reticence. Although reticence is sometimes used for strategic reasons (e.g., to unjustifiably evade culpability), reticence is also used in many situations because it is more appropriate than apology and denial. By considering information diagnosticity and belief formation mechanisms through which verbal responses are evaluated, we hypothesized that the effectiveness of reticence vis-à-vis apology and denial depends on the nature of the original trust violation. The hypotheses were tested in a laboratory study of a simulated employment interview. Results indicate that, as a response to an integrity-based violation, reticence produces trust levels that are similar to those of apology but inferior to denial. As a response to a competence-based violation, reticence produces trust levels that are similar to those of denial but inferior to apology. Our results have important implications for those who might use reticence to respond to a perceived trust violation, and also for those who must judge another's reticence.